THE PRINCIPLE OF LEGAL BENEFITS OF DERADICALIZATION OF TERRORISM IN THE INDONESIAN CRIMINAL JUSTICE SYSTEM - Md. Shodiq; Abdul Rahmat (Faculty of Law, Universitas Pekalongan, 2023)
Indonesia as a country experiencing a transition from transition to democracy is marked by the strengthening of the flow of democracy and reforms are faced with the growing terrorist acts. Which has an impact on the destruction of infrastructure and a deep fear of the people to live, terrorism is a crime against humanity and then has a wide network of real and serious threats and at any time can jeopardize the security of the country, Counterterrorism can not be solved by just enforcing law with the approach of Hard Approach but also must be done with Soft approach approach . In this case is the approach of the Deradicalization Program, especially to the perpetrators of criminal acts of terrorism. In the implementation of the Deradicalization Program begins in the process of investigation, prosecution and judicial process so that the Deradicalization Program can be used as consideration of the judge of the judges to decide the criminal case of Terrorism so that the Value of Legal Use in Deradicalization Program is achieved and the perpetrators of terrorist crimes do not do the deed or repeat the actions.The method used in this research is normative legal research that is done as an effort to get the data needed in connection with the problem, the specification of the research is normative and empirical, the data used is primary data and secondary data consisting of primary legal materials and secondary law materials as well as tertiary law materials then for data analysis done with qualitative jurisdictional analytical method.The benefits of deradicalisation programs are counter terrorism, preventing radicalism, comparing ideologies, evading hate provocation, hostility in the name of religion, preventing society from indoctrination, and community participation rejecting terrorism. The current deradicalisation program should be re-supplied by the government and the wider community. Although there are no specific provisions on the deradicalization of terrorism in the Indonesian criminal law system, it is necessary to list the provisions related to the deradicalization program based on the legalization of the deradicalization program becoming the latest formulas for counter terrorism have links to ideology , Deradicalization can be related to the process of creating an environment that prevents the growth of radical movements by responding to the root causes that encourage the growth of radicals.